Implementation of Internal Control System in the Purchasing Accounting System at PT. Berkat Anugerah Plastik Nganjuk - East Java - Fauziyah, Latifatul; Anzelia, Deva; Aisy, Firyal I`zaaz; Kurniawan, Muhammad Aldri; Sahita, Elsa; Primaningtias, Maria Angela (Indonesian Journal of Sustainability Policy and Technology, 2025)
Purpose: This study aims to evaluate the implementation of the internal control system within the purchasing accounting system at PT Berkat Anugerah Plastik Nganjuk. The objective is to identify the effectiveness and reliability of internal controls in supporting accurate and secure purchasing transactions. Methods: The research uses a descriptive qualitative approach. Data were primarily collected through interviews with individuals directly involved in the company's purchasing and financial administration processes. Informants include family members of the owner who hold operational roles across different company locations, such as Nganjuk, Krian, and Balongbendo, East Java. Findings: The findings indicate that the internal control system at PT Berkat Anugerah Plastik is strongly influenced by familial relationships, with key positions in finance, procurement, and operations held by trusted family members. While this structure enhances trust and coordination, it also poses risks related to accountability and segregation of duties. Some control procedures are in place, but they are not well-documented or standardized, making consistent application across branches difficult. Implication: The study highlights the need to formalize and document internal control procedures to strengthen accountability and transparency. Clearly defining role boundaries and establishing standard operating procedures can enhance the company’s risk management and decision-making processes. Originality: This research offers a unique perspective by examining an internal control system shaped by family-based management. It contributes to the broader discourse on corporate governance in small and medium-sized family-owned enterprises in Indonesia.